The Influence of Medical Subspecialty on the Adherence to Hepatocellular Carcinoma Surveillance in Patients with Chronic Hepatitis B - Feuangwattana, Poorikorn; Sripongpun, Pimsiri; Jandee, Sawangpong; Kaewdech, Apichat; Chamroonkul, Naichaya (Siriraj Medical Journal, 2024)
Objective: This study aimed to determine the adherence rate of HCC surveillance in CHB patients at the largest tertiary hospital in Southern Thailand and identify patient and physician factors that influence it. Materials and Methods: This retrospective cohort study included patients with CHB who were followed up for more than 1 year between 2011 and 2019 at a tertiary care hospital in Thailand. Patients diagnosed with HCC within 6 months of their first visit were excluded. The rate of adherence with HCC surveillance was calculated using percentage of time up-to-date with HCC surveillance (PTUDS). Results: The mean age of 531 eligible patients at the time HCC surveillance started was 55.5 ± 9.26 years. The most common indications for surveillance were male over 40 years of age (41.2%), female over 50 years of age (28.9%), and cirrhosis (22.6%). The median PTUDS was 70.6% (interquartile range 55.1 – 81.4%). The highest PTUDS was for cirrhosis (74.0%). For physicians’ subspecialties, the median PTUDS was 71.8% for gastroenterologists (IQR 58.3 – 81.6%) and 41.7% for internists (IQR 31.4 – 65.8%). Factors associated with increased PTUDS by multivariable analysis were having ≥2 clinical visits per year (±18.4%, p<0.001), civil servant reimbursement (±8.81%, p=0.001), cirrhosis (±6.06%, p=0.003), and being follow-up by gastroenterologists (±20.4%, p<0.001). Conclusion: The adherence with surveillance program in patients with CHB being followed up at a tertiary care setting in Thailand was good. This finding underscores the importance of education regarding indications for HCC surveillance, particularly in patients without cirrhosis.